ENCEPHALOPATY AKUT PADA ANAK DENGAN KELAINAN METABOLISME BAWAAN (PENDEKATAN PRAKTIS) - Puryatni, Anik; de Koning, Tom J. (Jurnal Kedokteran Brawijaya, 2008)
ABSTRACT Acute  encephalopathy  is  a  not  a  common,  but  a  potential  emergency  situation  in  newborns  and  youngchildren.  If  the  encephalopathy  is  not  caused  by  asphyxia  or  infections  of  the  brain,  rare  inborn  errors  ofmetabolism need to be considered. An acute encephalopathy due to an inborn error can occur in newborns,young  infants,  or  even  in  childhood  and  is  not  always  easily  recognized  because  more  subtle  presentationscan  occur.  In  this  article  we  will  give  a  practical  guideline  to  the  diagnostic  approach  of  metabolic  diseasespresenting with acute neurological symptoms with an emphasis on treatable disorders and the application indeveloping  countries  with  limited  diagnostic  resources.  The  first  step  in  the  evaluation  of  patient  with  apossible  metabolic  disease  is  to  categorise  the  clinical  appearance  of  the  patient  in  one  of  the  followingclinical categories: Hypoglycemia phenotype; Intoxication phenotype; Neurotransmitter defect phenotype; andCellular energy  metabolism defect  phenotype.  Second, combine this clinical classification with your physicaexamination  and  the  result  of  routine  laboratory  investigations  and  this  can  lead  to  suspected  diagnosis  ofmetabolic  disorders.Prompt  recognition  and  treatment  are  important,  because  an  acute  metabolicencephalopathy can irreversible and interruption of normal neural activity in the developing brain can have along-lasting  effect  on  psychomotor  development.  Delay  in  diagnosis  and  treatment  may  thus  result  in  acutemetabolic decompensation, progressive neurologic injury, or even death.  Key words: acute encephalopathy, inborn error metabolisme